Missed infection control care and healthcare associated infections: A qualitative study. Issue 4 (August 2021) - Bail, Kasia; Willis, Eileen; Henderson, Julie; Blackman, Ian; Verrall, Claire; Roderick, Allison
Abstract: Background: Research on missed nursing care reveals individual and systems failure. Research on infection control missed care is minimal. Aims: Investigate nurse perceptions of missed infection control. Design: Qualitative in-depth interviews with 11 Australian infection control nurse experts. Methods: Participants were asked whether nursing and hospital-wide care tasks fundamental to infection control were missed, and what were the underlying causes and contributing factors for these omissions. Qualitative data was mapped against fundamental nursing practice and Australian infection control guidelines. Findings: Omission of infection control care occur at the individual clinician and organisational level. Nurses describe failure to perform standard precautions as well as failure to perform basic care activities. Participants identified a range of institutional and cultural factors which contributed to cascade iatrogenesis resulting in healthcare associated infections for patients. Some factors are outside nurses' control and include: environmental cleanliness; ward layout; ward culture; resourcing and staffing; integration of infection control into clinical governance; action following audit results; and reviewing evidence base of protocols. Discussion: Care occurs in complex and conflicted settings, with prioritisation essential. Potentially harmful practices are generally done with the intention of care. Nurses are key, but not sole performers in the creation of quality infection control. Conclusion: Mapping missed care related to infection control against standard frameworks of nursing practice revealed "gaps in the chain of infection" that contribute to "cascade iatrogenesis" with negative outcomes for patients.